The Effect of Marriage Anxiety on Pre-pregnancy Fear of Birth in Single Women - ÜNAL, Esra; AĞRALI, Cansu; TİMUR TAŞHAN, Sermin (Göbeklitepe Medical Science Journal, 2022)
This study was conducted to evaluate the effect of marriage anxiety on pre-pregnancy fear of childbirth in single women. There search is descriptive and relationship-seeking type. The sample of the study consisted of 343 single women. In the study, data were collected online via google form, using personal information form, Marriage Anxiety Scale and Pre-Pregnancy Fear of Birth Scale. The data were evaluated with descriptive statistics such as number, percentage, mean, standard deviation, as well as t test, anova, pearson correlation analysis, Cronbach’s alpha analysis and multiple linear regression analysis. In the study, it was determined that there was a significant relationship between women’s employment status, income level and presence of partners and the total score of the marriage anxiety scale(p<0.05). A moderately significant positive correlation was found between the Marriage Anxiety Scale of single women and the total mean score of the Pre-Pregnancy Fear of Birth Scale (r=0.302; p<0.001). It was determined that there was no significant relationship between the women’s age, education level, duration of partner partnership, parental relationship status, knowledge about birth and future birth style preference and the total score of the marriage anxiety scale (p>0.05). As a result of the regression analysis, it was determined that the presence of a partner and the pre-pregnancy fear of childbirth scale score were important predictive variable for marriage anxiety. In the study, it was determined that not having a partner and having a high fear of childbirth negatively affect marriage anxiety.